ФОРМУВАННЯ ПРОФЕСІЙНОЇ МОТИВАЦІЇ СТУДЕНТІВ (Педагогіка вищої та середньої школи, 2010)
Some theoretical aspects of motivation and the results of practical research which are referred to study the components of motive sphere are viewed in the given article.